2018
DOI: 10.1093/mnras/sty606
|View full text |Cite
|
Sign up to set email alerts
|

Extreme star formation in the Milky Way: luminosity distributions of young stellar objects in W49A and W51

Abstract: We have compared the star-formation properties of the W49A and W51 regions by using far-infrared data from the Herschel infrared Galactic Plane Survey (Hi-GAL) and 850-μm observations from the James Clerk Maxwell Telescope (JCMT) to obtain luminosities and masses, respectively, of associated compact sources. The former are infrared luminosities from the catalogue of Elia et al., while the latter are from the JCMT Plane survey source catalogue as well as measurements from new data. The clump-mass distributions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 98 publications
(155 reference statements)
2
8
0
Order By: Relevance
“…This is consistent with the results of Eden et al (2015), who found an increased ratio of L/M, a proxy of SFE (e.g. Moore et al 2012;Eden et al 2015Eden et al , 2018, in the Perseus arm compared to the Scutum-Centaurus and Sagittarius spiral arms. However, this was found to be due to distinctly different time gradients for star formation across the spiral arms, with the Perseus star formation at a more advanced stage.…”
Section: Star Formation Across Different Spiral Armssupporting
confidence: 92%
“…This is consistent with the results of Eden et al (2015), who found an increased ratio of L/M, a proxy of SFE (e.g. Moore et al 2012;Eden et al 2015Eden et al , 2018, in the Perseus arm compared to the Scutum-Centaurus and Sagittarius spiral arms. However, this was found to be due to distinctly different time gradients for star formation across the spiral arms, with the Perseus star formation at a more advanced stage.…”
Section: Star Formation Across Different Spiral Armssupporting
confidence: 92%
“…As the W49 region is known to contain significantly higher densities on smaller spatial scales that are not resolved by the observations presented in this work (e.g. Vastel et al 2001;Eden et al 2018). The line emission could then emit from these compact regions that are heavily beam diluted in the observations presented in this work.…”
Section: Focusing On the "Dense" Gas Within W49amentioning
confidence: 73%
“…Higher resolution observations have shown that much sub-structure exists within W49A on scales much smaller than this beam size, which would then not be resolved with these observations (Galván-Madrid et al 2013). For example, using James Clerk Maxwell Telescope and higher-resolution Herschel observations, Eden et al (2018) identified ∼ 50 compact sources within the central ∼ 60 pc of W49A that have effective radii ranging from 10−20 (∼ 0.2 -0.3 pc). These cores have masses of > 10 3 M , which when assuming a spherical geometry approximately have column densities of > 10 23 cm −2 .…”
Section: Caveatsmentioning
confidence: 94%
See 2 more Smart Citations